2006
DOI: 10.1038/sj.eye.6702453
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of de-epithelialized amniotic membrane transplantation and conjunctival autograft after primary pterygium excision

Abstract: Purpose To study the efficacy of deepithelialized amniotic membrane (AM) graft (AmbioDry, Okto Ophtho Inc., Costa Mesa, CA, USA) as an adjunctive therapy after primary pterygium excision in comparison to standard conjunctival autograft. Methods A retrospective review of 23 eyes of 22 patients receiving pterygium excision followed by AM transplantation was performed. The results were compared retrospectively with 40 eyes of 36 patients receiving conjunctival autograft after pterygium excision. All patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…However, amniotic membrane, mitomycin C, and bare sclera recurrence rates reported in studies of primarily Hispanic patients have also been high. 10,11,[13][14][15][16] There remains a need for a prospective randomized trial to accurately delineate the role of Hispanic ethnicity in pterygium recurrence. Despite the limitations of a retrospective trial, our findings are consistent with the growing body of evidence, implicating the role of Hispanic ethnicity in the recurrence of pterygium after CAG.…”
Section: Discussionmentioning
confidence: 99%
“…However, amniotic membrane, mitomycin C, and bare sclera recurrence rates reported in studies of primarily Hispanic patients have also been high. 10,11,[13][14][15][16] There remains a need for a prospective randomized trial to accurately delineate the role of Hispanic ethnicity in pterygium recurrence. Despite the limitations of a retrospective trial, our findings are consistent with the growing body of evidence, implicating the role of Hispanic ethnicity in the recurrence of pterygium after CAG.…”
Section: Discussionmentioning
confidence: 99%
“…8D) (78,79). In cases with very large conjunctival defects created following pterygium excision, or if a proper autologous conjunctival graft cannot be harvested, an alternative technique is the use of preserved amniotic membrane, which is readily commercially available and provides an excellent substrate for epithelial regrowth (80). The use of more sophisticated conjunctival surgery is associated with considerably lower recurrence rates, often less than 10% (16,78).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Fifteen potentially relevant studies were identified [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Ten studies [16][17][18][19][20][21][22][23][24][25] were excluded from further analysis: two were excluded because they were not relevant [16,17], two were excluded because combined surgical modalities for patients were used [18,19], and six were excluded because there was insufficient information for calculating lnHR or var(lnHR) [20][21][22][23][24][25].…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Ten studies [16][17][18][19][20][21][22][23][24][25] were excluded from further analysis: two were excluded because they were not relevant [16,17], two were excluded because combined surgical modalities for patients were used [18,19], and six were excluded because there was insufficient information for calculating lnHR or var(lnHR) [20][21][22][23][24][25]. A total of five studies remained eligible for pooling risk estimates [11][12][13][14][15].…”
Section: Eligible Studiesmentioning
confidence: 99%